Characterization of peripheral immune cells in kidney transplantation recipients under different immunosuppressive treatments - Tai, Yunze; Li, Nanjing; Fan, Jiwen; Zhang, Haohan; Long, Honghui; Yan, Lin; Feng, Weihua; Zhang, Junlong; Cai, Bei; Fan, Yu; Luo, Yao; Li, Yi (Frontiers in Immunology, 2025)
BackgroundA comprehensive peripheral immune cell characterization including novel immunosuppressive subsets myeloid-derived suppressive cells (MDSCs) in kidney transplant recipients (KTRs) under different immunosuppressive treatments can help: 1) Immunosuppression situation and allograft acceptance assessment; 2) Infection and rejection emergence indication; 3) Beneficial immunosuppressive regimens’ selection.Methods26 KTRs with an average transplant duration of 360 days and 13 healthy controls were enrolled in this study. 11KTRs were included in the SRL-based therapy group and the other 15 in the TAC-based therapy group. Flow cytometry was used to detect the percentages and absolute numbers of MDSCs, T cell populations, HLA-DR+ monocytes, neutrophil CD64 index, and cytokines in peripheral blood.ResultsIn KTRs, the expression of G-MDSCs and M-MDSCs was significantly higher than the HCs, while the expression of HLA-DR+ monocytes, CD38+/CD28+ activated T cells, CD4+ naïve T cells, CD4+ effector memory T cells, and central memory T cells were significantly lower. The use of mTOR inhibitors in KTRs induced changes in the distribution of activated and naïve-memory T cell subsets and decreased proinflammatory cytokines.DiscussionIn KTRs, G-MDSCs and M-MDSCs accumulated while functionally activated, naïve-memory T cell populations and HLA-DR+ monocytes markedly decreased one year after transplantation. Additionally, the number of MDSCs and T cell subsets following transplantation is likely regulated by mTOR inhibitors.